Effects of resistant starch on glycemic response, postprandial lipemia and appetite in subjects with type 2 diabetes. - García-Vázquez, Carlos; Ble-Castillo, Jorge L.; Arias-Córdova, Yolanda; Ramos-García, Meztli; Olvera-Hernández, Viridiana; Guzmán-Priego, Crystell G.; Martínez-López, Mirian C.; Jiménez-Domínguez, Guadalupe; Hernández-Becerra, Josafat A. (European Journal of Nutrition, 2023)
Purpose: Resistant starch (RS) content has exhibited beneficial effects on glycemic control; however, few studies have investigated the effects of this substance on postprandial responses and appetite in subjects with type 2 diabetes (T2D). Here, we aimed to examine the effects of RS from two sources on glycemic response (GR), postprandial lipemia, and appetite in subjects with T2D. Methods: In a randomized and crossover study, 17 subjects with T2D consumed native banana starch (NBS), high-amylose maize starch (HMS) or digestible maize starch (DMS) for 4 days. On day 5, a 6-h oral meal tolerance test (MTT) was performed to evaluate glycemic and insulinemic responses as well as postprandial lipemia. Besides, subjective appetite assessment was measured using a visual analogue scale. Results: NBS induced a reduction on fasting glycemia, glycemia peak and insulinemic response during MTT. However, no modifications on postprandial lipemia were observed after RS treatments. Both NBS and HMS reduced hunger and increased satiety. Conclusion: NBS supplementation induced more beneficial effects on glycemic metabolism than HMS even when all interventions were matched for digestible starch content. RS intake did not modify postprandial lipemia, however, positively affected subjective appetite rates. Trial registration: This trial was retrospectively registered at www.anzctr.org.au (ACTRN12621001382864) on October 11, 2021.